Cultura: ¿un derecho para todxs? Propuesta de investigación-acción en derechos culturales - Pacheco Mariselli, Martha (2023)
This article aims to reflect on a challenging process of artistic creation of collective writing from an anthropological perspective, arising from academic research, around which a clown performance event was built. This scenic event, in turn, proceeded to be transferred from its original live performance format to an audiovisual recording format of that same performance. The transition from a situation of simultaneous presence of the clown and his audience, to another where the corporeal, sensory, emotional participation of the audiences is “mediated” by the production decisions that “compose” a “gaze” expressed by the camera that, as deferred “narrator,” assumes the leadership of an expressive communication process about the human values and emotions defined by a culture, in front of an anonymous audience. Confronting the initial challenge of finding significant expressive ways to “translate” the legal discourse (abstract, with a bias of supposed universality assumed to be homogeneous) on human rights and citizenship, a proposal was progressively developed, one that intuitively combined within a general logic of action research, strategies of collective creation, artistic performance research, specificallyclown, as well as the design of a technical proposal for audiovisual media that suggests an explanation of cultural rights (core part of the human rights set) as basis for the full exercise of an also expanded definition of citizenship; one based on cultural diversity, and its mark in the identity generation processes.